Improvements in Gait With Hearing Aids and Cochlear Implants. Issue 4 (April 2017) - Shayman, Corey S.; Earhart, Gammon M.; Hullar, Timothy E.
Abstract : Objective: To evaluate whether wearing auditory assistive devices can improve gait and dynamic balance. Patients: Three adult users of bilateral hearing assistive devices: one with cytomegalovirus exposure wearing cochlear implants, one with Ménière's disease wearing hearing aids, and one with presbystasis wearing hearing aids. Intervention: Rehabilitative intervention involved participants performing gait and dynamic posture tasks with and without their hearing assistive devices. Main Outcome Measures: Gait velocity and Mini-BESTest score. Results: The participant with Ménière's disease showed a clinically significant improvement in gait in the aided versus the unaided condition (20.5 cm/s higher velocity and five point better Mini-BESTest score). The other two participants also improved with augmented audition, but to a lesser degree. Conclusions: Bilateral hearing augmentation may promote clinically significant improvements in gait, although the effects are not uniform among patients. Hearing aids or cochlear implants may be important interventions for improving stability during walking in some people with hearing loss.